Dampak Pandemi Covid-19 terhadap Peternakan Hewan Qurban di Kota Sukabumi dan Kabupaten Bogor, Studi Kasus: Zona Hijau dan Merah - A. Hakim; P. Sembada; S. D. S. Andik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Corona Virus Disease 2019 (Covid-19) has been declared by the World Health Organization (WHO) as a pandemic and Indonesia is one of the countries affected by the outbreak. This has a major impact on the social economic and the prosperous community, especially for sub sector livestock which contributes to the fulfillment of the nutritional value of animal protein and national food security. This study aims to determine the impact of the Covid-19 pandemic on the livestock sector, especially to the sacrificial animal farm. Direct interviews using a questionnaire were conducted with 36 sacrifial animal farmers in the area of the Covid-19 spread map in the red zone (Bogor Regency) and the green zone (Sukabumi City) from September to November, 2020. The questionnaire was divided into three parts, first part about characteristics of farmers, second part about farming activities, and the last about market of sacrificial animals. The pandemic has caused changes in livestock procurement in terms of input prices and sales of sacrificial animals. The price of livestock for the production input during the pandemic in the green zone is low, while in the red zone is high. The decrease in sales occurred in the green zone, while in the red zone is increase, both for sheep and cattle farmers. Most of sacrificial animal farmers (88.89%) did not change their sales method from the previous year. Sacrificial animal farmers also strongly agree that Covid-19 pandemic has an impact on the economic conditions of farmers.